Spectrophotometric Study of W(VI)-G Lycinamide Complex Formation - Tajodini, Niloufar; Moghimi, Ali (Asian Journal of Chemistry, 2011)
The formation constants of W(VI)-glycinamide system were determined in buffer solution, pH = 4.0 (I = 0.1 mol L-1 in NaClO4 at 10, 15, 20, 25, 30 ºC) using UV-visible spectrophotometric method. The optical absorption spectra of W(VI)-glycinamide system were analyzed in order to obtain formation constants and stoichiometries based on SQUAD software. Determining the formation constants at various temperatures enabled us to calculate some thermodynamic parameters as K, DGº, DHº and DSº related to the considered complexes.